Differences in soil Cd immobilization and blockage of rice Cd uptake by biochar derived from crop residue and bone − A 2-year field experiment - Zhongjun Xue; Fengfeng Sui; Yanjie Qi; Siyu Pan; Ning Wang; Rongjun Bian; Stephen Joseph; Xuhui Zhang; Lianqing Li; Genxing Pan (Ecotoxicology and Environmental Safety)
Biochar is widely recognized as an effective amendment for soils contaminated with cadmium (Cd). However, the properties and elemental compositions of biochar derived from different feedstocks may significantly impact the transfer of Cd in the soil-rice system. This study conducted a two-year field trial in Cd-contaminated paddy soil. Rapeseed straw biochar (REB), rice husk biochar (RHB), and bone char (BOC) were applied once at rates of 0 t ha−1 (CK) and 15 t ha−1, respectively. The results indicated that biochar significantly decreased grain Cd concentrations by on average of 60.1 % and 22.9 % in 2021 and 2022, respectively. BOC significantly decreased CaCl2-Cd concentration by on average of 52.1 % and 64.7 % during two rice growing seasons, which was higher than that of crop biochar (22.7 % and 17.8 %). Soil exchangeable Ca and dissolved P in BOC treatment were higher, and had significantly negatively correlated with CaCl2-Cd (r = -0.50; r = -0.724). REB with higher S content efficiently increased the proportion of organics and sulfides bounding Cd. Except for BOC, REB and RHB significantly enhanced Cd fixation in IP by 44.4 %-92.0 % and 42.8 %-59.5 % in two years, in which IP-bound Fe and IP-bound Cd in REB were by 10.9 % and by 9.11 %-27.4 % higher than those of RHB respectively. The electron donating capacity of REB was 2.21-folds higher than that of RHB, which could promote IP formation by enhancing Fe(Ⅲ) reduction. RHB decreased Cd transformation from roots to shoots by 20.6 %-30.3 % compared to REB and BOC. Higher Si content in rice root in RHB treatment may promote complexation and deposition of Si hemicellulose-bound Cd in the root cell walls. This study reveals the important role of biochar's elemental composition and properties in soil Cd immobilization and the mitigation of rice Cd uptake.